Si vis pacem, para bellum - wizja rzymskiej armii i sztuki wojennej w świetle "Epitome rei militaris" Wegecjusza - Łuć, Ireneusz (Vox Patrum, 2020)
Paraphrase cited in the title of this article, that: “if you want peace, prepare for war” there is strictly refers to the thoughts of Vegetius, which he included in his „Epitome of Military Science”. Vegetius’ treatise was addressed to Roman commanders, officers and soldiers. For them, as Vegetius emphasized, a military knowledge was simply necessary to be brave in battles. Roman soldiers, knowing the "rules" governing war, should not be afraid of it, because, according to Vegetius' suggestion, no one is afraid to do what he is sure he has learned well. Although the content of the Epitoma rei militaris referred not only to the recruitment and training of recruits, the fact that author of this treatise devoted so much attention in his narrative to these issues there seems to best testify in what he actually saw the source of the most serious problems in the functioning of Roman legions that were part of the Roman army. The solutions outlined by Vegetius there were to improve the efficiency and military strength of these Roman units. Vegetius, writing his treatise, believed that thanks to the restoration of the best methods of recruitment, training and military organization, it would be possible to fix the errors of previous years and what’s more, it allowed restoring the Roman army to its former power, to dominate once again and terrify the enemies of the Roman state. Unfortunately, the coming time will inevitably verify his expectations.